2013
DOI: 10.1037/a0030512
|View full text |Cite
|
Sign up to set email alerts
|

Speed–accuracy trade-off in skilled typewriting: Decomposing the contributions of hierarchical control loops.

Abstract: Typing performance involves hierarchically structured control systems: At the higher level, an outer loop generates a word or a series of words to be typed; at the lower level, an inner loop activates the keystrokes comprising the word in parallel and executes them in the correct order. The present experiments examined contributions of the outer-and inner-loop processes to the control of speed and accuracy in typewriting. Experiments 1 and 2 involved discontinuous typing of single words, and Experiments 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 72 publications
(164 reference statements)
4
45
2
Order By: Relevance
“…In fact, corrected errors in their study were associated with post-error speeding where post-error key-presses were found to be faster than pre-error key-presses. Our findings partially support their interpretation in that PES following uncorrected errors in the absence of inhibition of backspace was much smaller than those reported in studies where participants are not allowed to correct their errors (usually several hundred ms in Snyder et al, 2014;Wilbert & Haider, 2012;Yamaguchi et al, 2013, as opposed to the current PES of 39ms). However, we did find that PES was statistically significant even though our participants were free, and in fact encouraged, to use the backspace to correct their errors.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In fact, corrected errors in their study were associated with post-error speeding where post-error key-presses were found to be faster than pre-error key-presses. Our findings partially support their interpretation in that PES following uncorrected errors in the absence of inhibition of backspace was much smaller than those reported in studies where participants are not allowed to correct their errors (usually several hundred ms in Snyder et al, 2014;Wilbert & Haider, 2012;Yamaguchi et al, 2013, as opposed to the current PES of 39ms). However, we did find that PES was statistically significant even though our participants were free, and in fact encouraged, to use the backspace to correct their errors.…”
Section: Discussionsupporting
confidence: 87%
“…For example, if errors are more frequent during slower (or faster) than average speed typing, such a baseline would be more sensitive to 'local' changes in typing speed. When participants try to type faster than their usual typing speed (Yamaguchi, Crump, & Logan, 2013) or too slowly, their chances of making mistakes may increase.…”
Section: Behavioural Analysismentioning
confidence: 99%
“…On each trial, words and nonwords are presented well before a go signal that instructs typists to start typing. Thus, much of the outer-loop processing might have been completed when the go signal was presented (Yamaguchi, Crump, & Logan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated dissociations between the two loops (e.g., Abrahamse, Ruitenberg, de Kleine, & Verwey, 2013;Crump & Logan, 2010a, b;Logan & Crump, 2009, 2010Snyder & Logan, 2013;Tapp & Logan, 2011;Verwey, 1999;Yamaguchi & Logan, 2014;Yamaguchi, Logan, & Li 2013b), but few studies have addressed how they work together to control typing (Yamaguchi, Crump, & Logan 2013a). The inner loop is subordinate to the outer loop (Logan & Crump, 2011), so inner-loop processes are subject to outer-loop processes.…”
Section: Hierarchical Control Of Skilled Typingmentioning
confidence: 99%